Maternal Mental Health. Issue 1 (January 2022) - Simpson, Kathleen Rice
Abstract : Approximately 1 out of 5 women experience a mental health condition such as anxiety or depression during pregnancy or postpartum. Routine screening and timely referral and treatment are key to promoting optimal outcomes for mothers and babies. While screening during postpartum visits is becoming more common, adding screening for mothers of babies in the NICU and during well baby visits can help to make sure all new mothers are included.